2007
DOI: 10.1016/j.lungcan.2006.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of clinical factors and Akt activation in patients with bronchioloalveolar carcinoma

Abstract: Purpose: Lung cancer is the leading cause of cancer related mortality in the world. BAC is a subset of NSCLC that has recently gained attention because of distinct biologic and clinical features, increased incidence, and enhanced responsiveness to new therapies such as epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs). However, prognostic features for BAC have not been well defined. Because activation of Akt is highly prevalent and a poor prognostic factor for other types of NSCLC, we ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 33 publications
(27 reference statements)
3
19
0
Order By: Relevance
“…This result was in accordance with the study (in press) by Tsurutani et al 15 in which they found that 95% of all the lung cancer patients had Akt expression. The pAkt expression was reported to be observed both in cytoplasm and nu-cleus according to the previous reports 16,17 but we observed in nucleus only.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result was in accordance with the study (in press) by Tsurutani et al 15 in which they found that 95% of all the lung cancer patients had Akt expression. The pAkt expression was reported to be observed both in cytoplasm and nu-cleus according to the previous reports 16,17 but we observed in nucleus only.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, it was recently reported that there was not found any association with Akt and the survival. 15 In our study, we found a positive correlation between pAkt and PTEN expressions although a negative correlation was also reported. 22 In contrast to these two different findings, it was also reported that there was no correlation between Akt and PTEN.…”
Section: Discussionsupporting
confidence: 61%
“…Percentages of adenocarcinoma in individual studies ranged from 17.3% to 100%. 51,66,67) Disease stages included varied from study to study; some studies analyzed only stage IA disease undergoing complete resection, 46,53,62,65) while some others included only unresectable stage IIIB and IV patients scheduled for chemotherapy or chemoradiotherapy. 56,59,75) Final statistical analyses used either univariate or multivariate analyses, or both.…”
Section: Resultsmentioning
confidence: 99%
“…Activated PI3K initiates the activation of the downstream kinase Akt. Moreover, phosphorylated Akt could facilitate cell survival and proliferation and regulate various signaling pathways (29)(30)(31). It has been shown that the activation of PI3K and Akt could inhibit autophagy (32).…”
Section: Discussionmentioning
confidence: 99%